Soil respiration and its temperature sensitivity in Pinus koraiensis plantations are mediated by temperature, humidity, and wind speed - Lianqiang Li; Huixia Yang; Hongyu Li; Jiatong Sun; Fuqiang Shang (Trees, Forests and People)
Soil respiration (RS) plays a key role in the carbon cycle which is sensitive to climate change. Therefore, understanding potential regulatory mechanisms of RS and its temperature sensitivity(Q10) in plantations are important. In this study the changes in RS and its Q10 along with their potential environmental driving factors of surface soil of Pinus koraiensis plantations in the Liaodong mountain area of Liaoning Province were studied. The results showed that variation in RS of the plantations is significant and unstable, whereas the variation in Q10 is relatively small and stable. RS was significantly positively correlated with soil temperature, soil moisture, air temperature, and air humidity, and negatively correlated with wind speed; Q10 was significantly positively correlated with air humidity and soil moisture, and negatively correlated with wind speed. Soil moisture and soil temperature accounted for 58 % and 35 % variability in RS, respectively, whereas air humidity and wind speed accounted for 25 % and 11 % variability in Q10, respectively. This study reveals that RS and its Q10 in Pinus koraiensis plantations are significantly mediated by temperature, humidity, and wind speed, and thus, this study has significant implications on soil carbon cycling in plantations under changing climate.